Arthroscopy-Assisted Management of Schatzker Type III Lateral Tibial Plateau Fracture With Interference Screw Fixation - Krzysztof Hermanowicz, M.D., Ph.D.; Tomasz Mrozek, M.D.; Adrian Góralczyk, M.D.; Konrad Malinowski, M.D., Ph.D. (Arthroscopy Techniques, 2021)
Tibial plateau fractures occur in both old and young patients and may be caused by low-energy trauma, as well as high-energy trauma. Owing to the variety of injury mechanisms and fracture patterns, tibial plateau fractures are very challenging to treat. One of the most demanding fractures is the type III fracture according to the Schatzker classification, which is a pure depression of the lateral tibial plateau. Treatment with open surgical procedures is associated with vast soft-tissue trauma and prolonged recovery after surgery. Although soft-tissue trauma is minimized and visual control is improved throughout arthroscopy-assisted surgical procedures, internal fixation using buttress plates or lag screws is still required to reduce and fix the depressed plateau. We present an arthroscopy-assisted technique of reduction and fixation of the lateral tibial plateau fracture with 3 BioComposite interference screws (Arthrex, Munich, Germany) that provides a high amount of stability and reduces patient immobilization, allowing for faster rehabilitation.